Analyzing ecological footprint through the lens of globalization, financial development, natural resources, human capital and urbanization - Arzoo Abid; Muhammad Tariq Majeed; Tania Luni (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This study aims to analyze the relationships of globalization, financial development, natural resources, human capital, and urbanization with ecological footprint employing a panel of 118 countries from 1971 to 2018. Further, for deeper insights, the analysis is extended for the panels of heterogeneous income groups namely high income (45), uppermiddle-income (27), lower-middle-income (30), and low-income (10) panels. For empirical analysis fully modified ordinary least squares (FMOLS), dynamic ordinary least squares (DOLS) methods are employed. The results show that economic growth improves environmental quality by lowering ecological footprint (EF). However, economic growth increases the ecological footprint in lower-middle-income countries. Globalization increases ecological footprints. Human capital increases environmental degradation by increasing EF footprint across all panels. Energy use increases EF in all income groups except the low-income group. Natural resources exert a positive influence on ecological footprint across all income groups except global and upper-middle-income countries. Urbanization increases the ecological footprint for all income panels except high-income economies. Financial development increases ecological footprint across all panels except lower-middle-income economies. The robustness analysis also validated our findings. The findings also hold for Belt and road, BRICS, G7, MENA, and OECD economies.
Keywords: 330; ecological footprint; energy consumption; environmental quality; financialdevelopment; globalization; human capital; natural resources; urbanization